Antioxidant activity of Artocarpus altilis (Parkinson) Fosberg leaves - Sikarwar, Mukesh S.; Hui, Boey Jia; Subramaniam, Kumutha; Valeisamy, Bavani Devi; Yean, Ling Kar; Balaji, Kaveti (Free Radicals and Antioxidants)
Objective: This research was aimed to investigate the antioxidant activity of Artocarpus altilis (Parkinson) Fosberg leaves. Materials and Methods: 2,2 diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and thiobarbituric acid (TBA) methods were used to determine the antioxidant activity with ascorbic acid as a reference. Results: Total phenolic content was found to be 26.22 mg gallic acid equivalents/g. In DPPH assay, the maximum free radical scavenging activity of the extract was found to be 70.59%. The TBA method also supported the antioxidant potential of the plant extract. Conclusion: From this detailed study, it can be concluded that the ethanolic extracts of A. altilis leaves possess moderate antioxidant property. It may be due to the presence of a modest amount of phenolic compounds in the leaves of this plant. Hence, the ethanolic extract of this plant may not act as first-line antioxidant defense but may be used as supportive antioxidant agent.
Keywords: Antioxidant activity; Artocarpus altilis; 2 2 diphenyl-1-picrylhydrazyl